Triterpenes Drug Delivery Systems, a Modern Approach for Arthritis Targeted Therapy - Célia Faustino; Noélia Duarte; Lídia Pinheiro (MDPI AG, 2023)
Arthritis is a major cause of disability. Currently available anti-arthritic drugs, such as disease-modifying anti-rheumatic drugs (DMARDs), have serious side-effects associated with long-term use. Triterpenoids are natural products with known anti-inflammatory properties, and many have revealed efficiency against arthritis both in vitro and in vivo in several animal models, with negligible cytotoxicity. However, poor bioavailability due to low water solubility and extensive metabolism upon oral administration hinder the therapeutic use of anti-arthritic triterpenoids. Therefore, drug delivery systems (DDSs) able to improve the pharmacokinetic profile of triterpenoids and achieve sustained drug release are useful alternatives for targeted delivery in arthritis treatment. Several DDSs have been described in the literature for triterpenoid delivery, including microparticulate and nanoparticulate DDSs, such as polymeric micro and nanoparticles (NPs), polymeric micelles, liposomes, micro and nanoemulsions, and hydrogels. These systems have shown superior therapeutic effects in arthritis compared to the free drugs and are similar to currently available anti-arthritic drugs without significant side-effects. This review focuses on nanocarriers for triterpenoid delivery in arthritis therapy, including osteoarthritis (OA), rheumatoid arthritis (RA) and gout that appeared in the literature in the last ten years.